A survey of tobacco dependence treatment services in 121 countries - Piné-Abata, Hembadoon (Blackwell Publishing Ltd, 2013)
AIMS: To report progress among Parties to the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) in developing tobacco dependence treatment systems in accordance with FCTC Article 14 and the Article 14 guidelines recommendations. DESIGN: Cross-sectional study. SETTING: Electronic survey from December 2011 to August 2012. PARTICIPANTS: One hundred and sixty-three of the 174 Parties to the FCTC at the time of our survey. MEASUREMENTS: The 51-item questionnaire contained 21 items specifically on treatment systems. Questions covered the availability of basic treatment infrastructure and national cessation support systems. FINDINGS: We received responses from 121 (73%) of the 166 countries surveyed. Fewer than half of the countries had national treatment guidelines (n = 53, 44%), a government official responsible for tobacco dependence treatment (n = 49, 41%), an official national treatment strategy (n = 53, 44%) or provided tobacco cessation support for health workers (n = 55, 46%). More than half encouraged brief advice in existing health care services (n = 68, 56%), while only 44 (36%) had quitlines and only 20 (17%) had a network of treatment support covering the whole country. Low- and middle-income countries had less tobacco dependence treatment provision than high-income countries. CONCLUSION: Most countries, especially low- and middle-income countries, have not yet implemented the recommendations of FCTC Article 14 or the FCTC Article 14 guidelines.